TRIM28 Is an Epigenetic Barrier to Induced Pluripotent Stem Cell Reprogramming - Miles, Denise Catherine; de Vries, Nienke Alexandra; Gisler, Santiago; Lieftink, Cor; Akhtar, Waseem; Gogola, Ewa; Pawlitzky, Inka; Hulsman, Danielle; Tanger, Ellen; Koppens, Martijn; Beijersbergen, Roderick Leonardus; van Lohuizen, Maarten (Stem cells (Dayton, Ohio), 2017)
Since the discovery of induced pluripotent stem cells there has been intense interest in understanding the mechanisms that allow a somatic cell to be reprogrammed back to a pluripotent state. Several groups have studied the alterations in gene expression that occur as somatic cells modify their genome to that of an embryonic stem cell. Underpinning many of the gene expression changes are modifications to the epigenetic profile of the associated chromatin. We have used a large‐scale shRNA screen to identify epigenetic modifiers that act as barriers to reprogramming. We have uncovered an important role for TRIM28 in cells resisting transition between somatic and pluripotent states. TRIM28 achieves this by maintaining the H3K9me3 repressed state and keeping endogenous retroviruses (ERVs) silenced. We propose that knockdown of TRIM28 during reprogramming results in more plastic H3K9me3 domains, dysregulation of genes nearby H3K9me3 marks, and up regulation of ERVs, thus facilitating the transition through reprogramming. Stem Cells 2017;35:147–157 Model of TRIM28 function during reprogramming A) Ectopic expression of Oct4, Sox2, Klf4 and c‐Myc (OSKM) induces the reprogramming of somatic cells into induced pluripotent stem cells at a low efficiency B) Ectopic expression of OSKM along with knock down of TRIM28 increases the expression of genes nearby H3K9me3, and induces the expression of endogenous retroviruses. This decondensed chromatin state increases the reprogramming efficiency.